Supercritical carbondioxide extraction of cypermethrin in different fresh vegetables using anhydrous sodium sulfate for sample preparation and extraction - Rahman, Mohammad Arifur; Omar, Dzolkhifli; Sarker, Md. Zaidul Islam; Morshed, Md. Mahbub; Rashid, K. N. H. (Academic Journals, 2010)
Supercritical fluid extraction (SFE) is a promising method of extraction for pesticide residues in fruits and vegetables. A rapid and high percetage of recoveries extraction of cypermethrin insecticides from fresh yardlong bean, carrot and eggplant vegetables matrixs using drying agent and SC-CO2 was developed in this study. In vegetable samples, which typically contain 80 - 95% water, but samples dry with Na2SO4 showed 96 - 105% recoveries in SFE. Moreover, the performance of drying agents (Na2SO4) and their combination such as Na2SO4 –H2O (6.7 + 1),Na2SO4 – H2O (2 + 1) and Na2SO4 – H2O (1 + 1) were evaluated. Na2SO4-H2O (1 + 1) was shown moisture conveyanced by SFE/mg highest (93) performance.Cypermethrin recovered from yardlong bean and carrot with critical pressure, PC at 20 Ibs and critical temperature, TC 40°C. On the other hand, the recovery rate of similar insecticides from egg plant was 96% with PC at 31.5 Ibs and 45°C in TC.The recovery rate in yardlong bean matrices was 100%; 105% was in carrot matrix. The retention time (tR) was 49.6 min of cypermethrin standard and similar tR was found in formulated. The lowest detectable limit (LDL) of cypermethrin insecticides was 0.02 µg/mL with gas chromatography-electron capture detection (GC-ECD).GC-ECD temperature was of injection port and detector 280 and 300°C, respectively, with split less. However, the method is useful to recover non-polar insecticides from the fresh vegetable; thus, further research could be continued with co-solvents and different drying agents to recover the polar residues from different types of fresh vegetables.